2013
DOI: 10.1177/1359105313502564
|View full text |Cite
|
Sign up to set email alerts
|

Are child anxiety and somatization associated with pain in pain-related functional gastrointestinal disorders?

Abstract: This study investigated individual and incremental contributions of somatization and trait anxiety to pain report in children with pain-related functional gastrointestinal disorders. Eighty children (7–10 years) with pain-related functional gastrointestinal disorders completed the State-Trait Anxiety Inventory for Children, the Children’s Somatization Inventory, and 2-week pain diaries (assessing pain frequency and maximum pain). Hierarchical regressions indicated that both trait anxiety and somatization were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 60 publications
0
31
1
Order By: Relevance
“…Furthermore, a community‐based study in a nonclinical sample of children and adolescents, found that somatization mediated the relationships of anxiety/depression and abdominal pain . Williams and colleagues also reported that somatization is more strongly associated with pain severity than anxiety, although they did not test for mediation . Other studies suggest that these maladaptive thought processes may also affect other health outcomes in children with abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a community‐based study in a nonclinical sample of children and adolescents, found that somatization mediated the relationships of anxiety/depression and abdominal pain . Williams and colleagues also reported that somatization is more strongly associated with pain severity than anxiety, although they did not test for mediation . Other studies suggest that these maladaptive thought processes may also affect other health outcomes in children with abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists suggesting this same relation may be true for children. Our research group has shown somatization is associated with abdominal pain symptoms in children with functional abdominal pain . In a sample of healthy children without a functional abdominal pain disorder, Lavigne and colleagues found somatization mediated the relation between anxiety/depression and abdominal pain .…”
Section: Introductionmentioning
confidence: 87%
“…18 The CSI has been successfully used and validated in children with functional gastrointestinal disorders such as IBS. 19, 20 Total scores for the CSI range between 0 and 140 with increasing scores indicating greater levels of somatization.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, somatization is an important predictor of outcomes in children with FAPD. It is associated with pain severity, medical health visits, and pain maintenance into adulthood . Williams et al found somatization to be more strongly associated with pain severity than anxiety.…”
Section: Fapd and Somatizationmentioning
confidence: 99%
“…It is associated with pain severity, medical health visits, and pain maintenance into adulthood . Williams et al found somatization to be more strongly associated with pain severity than anxiety. Studies suggest that anxiety may only indirectly affect symptoms, through its effect on somatization .…”
Section: Fapd and Somatizationmentioning
confidence: 99%